2008
DOI: 10.1007/s00464-008-9777-3
|View full text |Cite
|
Sign up to set email alerts
|

Limb performance and patient satisfaction after radial artery harvesting: endoscopic versus open techniques

Abstract: After a mean of 9.8 months after surgery, patients reports good overall upper-limb function. However, more patients in the open technique had significant disabilities and dissatisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
(29 reference statements)
0
12
0
Order By: Relevance
“…Other retrospective observational studies, comparing endoscopic and open technique also showed reduction of wound healing and neurological complications, in favor of ERAH. Moreover, significantly reduced impairment in work and regular daily activities (0% vs.12%) and postoperative pain (0% vs. 8%) was observed 21 . Avoidance of long forearm skin incision in ERAH minimizes the risk of the LACN injury in contrast to ORAH.…”
Section: Discussionmentioning
confidence: 86%
“…Other retrospective observational studies, comparing endoscopic and open technique also showed reduction of wound healing and neurological complications, in favor of ERAH. Moreover, significantly reduced impairment in work and regular daily activities (0% vs.12%) and postoperative pain (0% vs. 8%) was observed 21 . Avoidance of long forearm skin incision in ERAH minimizes the risk of the LACN injury in contrast to ORAH.…”
Section: Discussionmentioning
confidence: 86%
“…This study compared radial artery harvest to vein harvest. There has also been a quality of life study comparing ERAH versus ORAH which used a short questionnaire devised by Medalion as outcome [24]. The questionnaire used in the RAPCO study seems more precise than the four questions used by Medalion, which is why it has been chosen for this trial.…”
Section: Methods and Designmentioning
confidence: 99%
“…The published studies differ in how the investigators examine the extent of neurological deficits. Most use non-specific neurological examinations and others only rely on questionnaires [24]. The most specific examination procedure seems to be used by Bleiziffer et al, who assessed the muscle strength, deep tendon reflexes, temperature, pain, and touch sensation [18].…”
Section: Introductionmentioning
confidence: 99%
“…Minimally invasive techniques have been proposed by many authors using endoscopic devices with superior outcomes. However, this approach is time consuming, needs expensive instrumentation, and has a significant learning curve 8‐11 …”
mentioning
confidence: 99%
“…However, this approach is time consuming, needs expensive instrumentation, and has a significant learning curve. [8][9][10][11] We present a tunneling radial artery harvesting technique under direct vision that is safe, less invasive compared to standard open technique, and cost-effective compared to endoscopic techniques. , 40 consecutive patients scheduled for coronary artery bypass grafting were randomly divided into two groups.…”
mentioning
confidence: 99%